Rosenblatt's Transactional Theory and Its Implementation in the Teaching of Integrated Reading - A.A. Istri Ngurah Marhaeni (Universitas Negeri Malang, 2016)
The transactional theory signifies that both the reader and the text play important roles in the formation of meaning. Meaning is produced by continuous transaction between the reader and the text, employing the meaning potential of the text and the reader's experiential reservoir. While the reader is active in selecting and synthesizing the potential in his reservoir, the text contributes to the shaping of his selection and hypotheses, resulting in an interplay between them. Reading and writing are interrelated skills in which the transactional theory is also applicable. The transactional theory provide some implications for the classroom language instruction. Then, an experience in doing journal writing for an English reading class, as one way to put the theory into practice, is presented.